2021
DOI: 10.3389/fpsyg.2021.611472
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Body Dissatisfaction With Lifestyle Behaviors and Socio-Demographic Factors Among Saudi Females Attending Fitness Centers

Abstract: ObjectiveTo examine body image perception and the associations of body dissatisfaction (BD) with socio-demographic and lifestyle factors among Saudi women attending fitness centers in Riyadh.MethodsSaudi females aged 16 years and older were recruited from 12 randomly selected fitness centers in Riyadh, using stratified clustered sampling technique (n = 460). Height and weight were measured to calculate actual body mass index (BMI). A previously validated instrument was used to collect socio-demographic and lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 59 publications
5
19
0
Order By: Relevance
“…Those who have been on a diet to lose weight or for therapeutic reasons had signi cantly lower body satisfaction scores than those who dieted for "other reasons". Similar to our ndings, a Saudi study reported that weight loss attempts were signi cantly associated with higher body dissatisfaction among women (Albawardi et al, 2021). Also an Emeriti study found that the percentage of body dissatis ed female university students and had been on a diet were higher than those who are satis ed with their bodies.…”
Section: Body Image and Lifestylesupporting
confidence: 89%
See 4 more Smart Citations
“…Those who have been on a diet to lose weight or for therapeutic reasons had signi cantly lower body satisfaction scores than those who dieted for "other reasons". Similar to our ndings, a Saudi study reported that weight loss attempts were signi cantly associated with higher body dissatisfaction among women (Albawardi et al, 2021). Also an Emeriti study found that the percentage of body dissatis ed female university students and had been on a diet were higher than those who are satis ed with their bodies.…”
Section: Body Image and Lifestylesupporting
confidence: 89%
“…Similarly, a study found that 87% of Saudi women attending tness centers were dissatis ed with their body shape (Albawardi et al, 2021). This difference might be caused by the difference in age group, as the Jordanian study reported that older women desired more weight change (Madanat et al, 2011), and older Saudi women had higher body dissatisfaction (Albawardi et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations